Answer:
(x - 3)^2 + (y + 1) = 25
Step-by-step explanation:
First find the midpoint of the diameter, because that represents the center of the circle.
-1 + 7
The x-coordinate of the midpoint is xm = ---------- = 3
2
2 - 4
and the y-coordinate is ym = ---------- = -1
2
And so the center of this circle is at (3, -1).
Use the Pythagorean Theorem to determine the square of the radius:
square of radius = 4^2 + (-3)^2 = 16 + 9 = 25
And so the equation of this circle is (x - 3)^2 + (y + 1) = 25
Answer:
12
+ 29x - 14
Step-by-step explanation:
(3x+2)(4x-7)
Multiply out 3x first then 2
(3x * 4x) - (3x * -7) + (2 * 4x) + (2 * -7)
12
- (- 21x) + 8x + ( -14)
12
+ 21x + 8x - 14 Combine like terms
12
+ 29x - 14
Answer:
i belive the answer should be x = 0
Step-by-step explanation:
Since two opposites add up to zero, remove them from the expression
and then 7=1 the statement is false for any value of x
Answer:
Out of every 5 rectangles 2 shall be purple.
3 scarves have 3 times 5 rectangles.
Thus they shall be 3 times 2 that are purple.
Step-by-step explanation:
There were 45 questions on the test. Hope this helps! <3